2023
DOI: 10.3390/ijms24054955
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium butyricum Prevents Dysbiosis and the Rise in Blood Pressure in Spontaneously Hypertensive Rats

Abstract: Hypertension is accompanied by dysbiosis and a decrease in the relative abundance of short-chain fatty acid (SCFA)-producing bacteria. However, there is no report to examine the role of C. butyricum in blood pressure regulation. We hypothesized that a decrease in the relative abundance of SCFA-producing bacteria in the gut was the cause of spontaneously hypertensive rats (SHR)-induced hypertension. C. butyricum and captopril were used to treat adult SHR for six weeks. C. butyricum modulated SHR-induced dysbios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In the fecal samples, the species of more abundant bacteria in the fecal samples (LDA > 2) were Lactobacillus hayakitensis, Lactobacillus equi, Lactobacillus amylovorus, Lactobacillus salivarius, Lactobacillus gastricus, Lactobacillus hamsteri and Lactobacillus acidophilus belonging to the Lactobacillus, which was the predominant microbes in the horse [31]. Lactobacillus amylovorus, a short-chain fatty acid (SCFA)-producing bacteria [32], has been reported to reduce weight and fat content in humans [33]. What's more, Lactobacillus amylovorus is a kind of Lactobacillus that can e ciently utilize starch, as a food and feed additive, it has been widely used for mildew prevention and antibacterial, bacteriostasis, and enzyme production [34].…”
Section: Discussionmentioning
confidence: 99%
“…In the fecal samples, the species of more abundant bacteria in the fecal samples (LDA > 2) were Lactobacillus hayakitensis, Lactobacillus equi, Lactobacillus amylovorus, Lactobacillus salivarius, Lactobacillus gastricus, Lactobacillus hamsteri and Lactobacillus acidophilus belonging to the Lactobacillus, which was the predominant microbes in the horse [31]. Lactobacillus amylovorus, a short-chain fatty acid (SCFA)-producing bacteria [32], has been reported to reduce weight and fat content in humans [33]. What's more, Lactobacillus amylovorus is a kind of Lactobacillus that can e ciently utilize starch, as a food and feed additive, it has been widely used for mildew prevention and antibacterial, bacteriostasis, and enzyme production [34].…”
Section: Discussionmentioning
confidence: 99%
“…In a study, the ginsenoside Rb1 group exhibited marked increases in the genera Clostridium, Roseburia, Ruminococcus, and Treponema (Wang et al, 2021). Another group showed that losartan, in addition to reducing blood pressure, increased the levels of Aristophanes, Lactobacillus, and Butyric acidophilus, while decreasing Ruminococcaceae, Streptococcus, and Turbotobacteria (Luo et al, 2023). Furthermore, a survey of the fecal microbiota demonstrated a positive association between specific Vibrio lachnosus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Ruminococcus bromii could produce butyrate in the colon by fermenting resistant starch [136]. The latest investigations suggest that butyrate prevents hypertension and inflammation [137]. Several recent clinical studies support that SCFAs play a beneficial role in the prevention and treatment of human diseases, such as regulation of cardio-metabolic outcomes [130], improvement of gut barrier integrity [138], regulating cardiac function [139], modulation of glucose and lipid metabolism [140], and mediation of the immune system promoting insulin secretion [141], increasing energy expenditure and reducing fat accumulation [142] and anti-inflammatory response [143].…”
Section: Production Of Metabolitesmentioning
confidence: 99%